1996
DOI: 10.1029/95jb01587
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term earthquake clustering: A 50,000‐year paleoseismic record in the Dead Sea Graben

Abstract: The temporal distribution of earthquakes in the Dead Sea Graben is studied through a 50,000‐year paleoseismic record recovered in laminated sediments of the Late Pleistocene Lake Lisan (paleo‐Dead Sea). The Lisan represents more than 10 times the 4000 years of historical earthquake records. It is the longest and most complete paleoseismic record along the Dead Sea Transform and possibly the longest continuous record on Earth. It includes unique exposures of seismite beds (earthquake‐induced structures) associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
235
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 360 publications
(252 citation statements)
references
References 45 publications
13
235
1
3
Order By: Relevance
“…3B). We note that clusters previously documented on plate-bounding faults are generally separated by pronounced periods of quiescence (8)(9)(10)(11)(12). In contrast, our results show that an earthquake cluster may be an anomaly in an otherwise quasiperiodic record, at least on intraplate faults.…”
Section: Fluid Infiltrationcontrasting
confidence: 54%
See 1 more Smart Citation
“…3B). We note that clusters previously documented on plate-bounding faults are generally separated by pronounced periods of quiescence (8)(9)(10)(11)(12). In contrast, our results show that an earthquake cluster may be an anomaly in an otherwise quasiperiodic record, at least on intraplate faults.…”
Section: Fluid Infiltrationcontrasting
confidence: 54%
“…However, an alternative view posits that spatial and temporal variations in fault strength and/or mechanical interactions between adjacent faults can lead to either a random or a clustered distribution of seismic events for a given fault (8)(9)(10)(11)(12)(13). This view has led to greater use of "time-independent" and clustered earthquake recurrence models.…”
mentioning
confidence: 99%
“…Similar aperiodic behavior was reported along the Dead Sea Fault zone [Marco et al, 1996]. Other examples of long-term analysis of seismic activity using historical catalogs [Ambraseys, 1989;Vere-Jones and Ozaki, 1982;Xu and Deng, 1996;Goes, 1996], paleoseismologic data [Jacoby et al, 1998;Grant and Sieh, 1995;Marco et al, 1996;Wells et al, 1999], geomorphological data [Ritz et al, 2003], or geodesic and geologic data [Friedrich et al, 2003] show that periods of activity can alternate with periods of quiescence along a single fault or a group of faults and that many fault zones exhibit temporal earthquake clustering [Pirazzoli et al, 1996].…”
Section: Discussionmentioning
confidence: 79%
“…[3] Historical earthquake records [Ambraseys, 1989;Vere-Jones and Ozaki, 1982;Xu and Deng, 1996;Goes, 1996] and paleoseismologic data [Jacoby et al, 1998;Grant and Sieh, 1995;Marco et al, 1996;Wells et al, 1999] have, however, shown that earthquake recurrence time and earthquake-related slip on a given fault can show great variations. These variations are yet poorly understood though several models predict irregular behavior [Bak and Tang, 1989;Carlson and Langer, 1989;Ben-Zion, 1996;Shaw and Rice, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…However, for other fault zones, discrepancies between geodetic and geologic rates are often observed, and have led to suggestions of complex behavior such as slip pulses, strain waves, and possible relations to earthquake clusters and other non-linear spatial-temporal deformation processes (Meade and Hager, 2005;Marco et al, 1996;Rockwell et al, 2000;Peltzer et al, 2001;Bennett et al, 2004;Friedrich et al, 2004;Oskin and Iriondo, 2004;Dolan et al, 2007;Oskin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%